Influencer Credibility and Authenticity in the Fight Against Misinformation - Phuong Vi Thi; Adamkolo Ibrahim (Feedback International Journal of Communication, 2025)
The rise of social media influencers has reshaped how information is produced and consumed. While their perceived authenticity grants them persuasive power, questions persist about the credibility of their content and the risks of misinformation. Algorithms that prioritize engagement over accuracy further exacerbate this paradox. This paper employs a narrative literature review, synthesizing findings from studies on influencer authenticity, misinformation dynamics, and digital trust. Sources include peer-reviewed journals, policy reports, and case-based analyses, with an emphasis on cross-disciplinary perspectives from communication studies, marketing, and digital ethics. The findings indicate that influencer credibility depends on multiple factors beyond audience size, including transparency, expertise, consistency, and accountability. While fact-checking tools, regulations, and media literacy programs are common strategies, they remain fragmented and reactive. A significant gap exists in influencer accountability and the lack of co-created ethical standards, leaving misinformation unchecked in many cases. Current approaches are limited by scalability, regulatory inconsistencies, and algorithmic bias that favors sensationalism. Addressing misinformation requires systemic change: engaging influencers as partners in setting ethical norms, rethinking algorithms to reward accuracy, and expanding media literacy across demographics. Future research should investigate empirical cases of influencer responsibility, audience trust dynamics across cultures, and platform-level reforms to ensure long-term resilience against misinformation.